2009
DOI: 10.1016/j.ijpara.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a fatty acid and retinol binding protein orthologue from the hookworm Ancylostoma ceylanicum

Abstract: Hookworms, bloodfeeding intestinal nematodes, infect nearly one billion people in resource limited countries and are a leading cause of anemia and malnutrition. Like other nematodes, hookworms lack the capacity to synthesize essential fatty acids de novo and therefore must acquire those from exogenous sources. The cDNA corresponding to a putative Ancylostoma ceylanicum fatty acid and retinol binding protein-1 (AceFAR-1) was amplified from adult hookworm mRNA. Studies using quantitative reverse transcriptase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 57 publications
(86 reference statements)
3
77
1
8
Order By: Relevance
“…Based on secondary structure analysis, the structure of FAR proteins are clearly unlike that of any family of lipid-binding proteins, and also structurally distinct from proteins known from any organisms-from bacteria to plants to humans, increasing the possibility that they may present useful targets for drug development [20].…”
Section: Previous Research On Parasitic Far Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on secondary structure analysis, the structure of FAR proteins are clearly unlike that of any family of lipid-binding proteins, and also structurally distinct from proteins known from any organisms-from bacteria to plants to humans, increasing the possibility that they may present useful targets for drug development [20].…”
Section: Previous Research On Parasitic Far Proteinsmentioning
confidence: 99%
“…Such an expansion of the analysis to include additional temperatures may be quite relevant, as previous research has demonstrated significant variation in the binding affinities of various proteins to their ligands with regard to environmental temperature [37], and nematodespecific FAR proteins have been shown to be heat-stable [13,20]. Given that plant-parasitic nematodes are much more prevalent during warmer seasons and in tropical climates [38][39][40] and that animal parasites would, by their nature, inhabit warmer environments, it seems possible that FAR studies conducted to date, at 20°C, may not accurately reflect the binding properties of this family of protein in vivo.…”
Section: Future Directions and Parasitic Fars As Targets In Drug Devementioning
confidence: 99%
“…These molecules have important functions as energy sources and are used in the metabolic and developmental processes of embryogenesis, glycoprotein synthesis, growth and cellular differentiation (Kennedy 2000;McDermott et al 1999). Based on secondary-structure analysis, the structure of FAR proteins is clearly unlike that of any family of lipid-binding proteins (Fairfax et al 2009). FAR proteins are structurally distinct,~20-kDa alphahelix-rich lipid-binding proteins that do not derive from larger polyproteins Prior et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, group A has the highest sequence identity to FAR proteins from parasitic nematodes, among them the plant parasitic FAR proteins of Globodera pallida (Gp-FAR-1), Meloidogyne javanica (Mj-FAR-1) and Aphelenchoides besseyi (Ab-FAR-1) (Cheng et al 2013;Iberkleid et al 2013;Prior et al 2001). FAR proteins have also been extensively found in parasitic nematodes of humans and animals, including Ancylostoma caninum, Brugia malayi, Brugia pahangi, Ancylostoma ceylanicum, Acanthocheilonema viteae, Ascaris suum, Heligmosomoides polygyrus, Onchocerca gutturosa, Onchocerca dukei, Onchocerca ochengi, Loa loa, Wuchereria bancrofti, and Litomosoides sigmodontis (Basavaraju et al 2003;Bath et al 2009;Fairfax et al 2009;Garofalo et al 2002;Mei et al 1997;Nirmalan et al 1999). Studies on animal-parasitic nematodes have indicated that they all belong to two major clusters and share high sequence similarity (79-100 %) (Marchler-Bauer et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…O fungo D. flagrans (AC001) apresentou atividade predatória sobre as L 3 de A. ceylanicum após o trânsito pelo trato gastrintestinal de hamsters. Além disso, foi observada uma diferença significativa nos percentuais obtidos de cada horário em relação ao numero de L 3 recuperadas (P < 0,01 The role of pet animals (dogs and cats) as reservoirs of potentially zoonotic nematodes has been recognized as a worldwide public health problem (FAIRFAX et al, 2009). Prominent among these nematodes is the genus Ancylostoma, which includes several species (A. caninum, A. braziliense and A. ceylanicum).…”
Section: Introductionunclassified